Immune responses against shared antigens are common in esophago-gastric cancer and can be enhanced using CD40-activated B cells. Issue 12 (9th December 2022) - Thelen, Martin; Keller, Diandra; Lehmann, Jonas; Wennhold, Kerstin; Weitz, Hendrik; Bauer, Eugen; Gathof, Birgit; Brüggemann, Monika; Kotrova, Michaela; Quaas, Alexander; Mallmann, Christoph; Chon, Seung-Hun; et al.
Abstract : Background: Specific immune response is a hallmark of cancer immunotherapy and shared tumor-associated antigens (TAAs) are important targets. Recent advances using combined cellular therapy against multiple TAAs renewed the interest in this class of antigens. Our study aims to determine the role of TAAs in esophago-gastric adenocarcinoma (EGA). Methods: RNA expression was assessed by NanoString in tumor samples of 41 treatment-naïve EGA patients. Endogenous T cell and antibody responses against the 10 most relevant TAAs were determined by FluoroSpot and protein-bound bead assays. Digital image analysis was used to evaluate the correlation of TAAs and T-cell abundance. T-cell receptor sequencing, in vitro expansion with autologous CD40-activated B cells (CD40Bs) and in vitro cytotoxicity assays were applied to determine specific expansion, clonality and cytotoxic activity of expanded T cells. Results: 68.3% of patients expressed ≥5 TAAs simultaneously with coregulated clusters, which were similar to data from The Cancer Genome Atlas (n=505). Endogenous cellular or humoral responses against ≥1 TAA were detectable in 75.0% and 53.7% of patients, respectively. We found a correlation of T-cell abundance and the expression of TAAs and genes related to antigen presentation. TAA-specific T-cell responses were polyclonal, could be induced or enhanced using autologous CD40Bs and were cytotoxic in vitro. Despite the frequent expression of TAAs co-occurrence with immune responses was rare. Conclusions: We identified the most relevant TAAs in EGA for monitoring of clinical trials and as therapeutic targets. Antigen-escape rather than missing immune response should be considered as mechanism underlying immunotherapy resistance of EGA.